Role of palladium crystallite size on CO oxidation over CeZrO 4-δ supported Pd catalysts - Burange, Anand S.; Reddy, Kasala Prabhakr; Gopinath, Chinnakonda; Shukla, Rakesh; Tyagi, Avesh K. (Journal of Molecular Catalysis, 2018)
Photodeposited palladium on nanocrystalline CeZrO 4-δ support was evaluated for CO oxidation, as a function of particle size and pre-treatment. All the catalysts were well characterized by XRD, SEM, EDX, TEM, CO chemi-sorption and Raman spectroscopy. It was observed that change in photodeposition time alters the average crystallite size of Pd, and the same was confirmed by CO chemisorption. 7 nm average crystallite size of Pd exhibited excellent catalytic activity for CO oxidation. In order to understand the effect of support and metal-support interaction, 1 wt% Pd was deposited deliberately onto reduced and oxidized CeZrO 4-δ support. The reduced support with anionic vacancies and more Ce 3+ species exhibited an improvement in CO oxidation at onset temperature. Detailed analysis shows that Pd-deposition occurs preferentially at oxygen-vacancy sites and subsequent metal-support interaction influences the catalysis.